A preliminary study on the formation pathways of glycated phosphatidylethanolamine of food rich in phospholipid during the heat-processing. Issue 21 (21st March 2018) - Lin, Qingna; Han, Lipeng; Liu, Guoqin; Cheng, Weiwei; Wang, Liqing
Abstract : The formation of food-derived glycated phosphatidylethanolamine (PE) in thermal process was investigated by designing a 1, 2-dipalmitoyl- sn-glycero -3-phosphoethanolamine (DPPE)-glucose model system heated from 40 to 100 °C for 8 h. Abstract : The formation of food-derived glycated phosphatidylethanolamine (PE) in thermal process was investigated by designing a 1, 2-dipalmitoyl- sn-glycero -3-phosphoethanolamine (DPPE)-glucose model system heated from 40 to 100 °C for 8 h. The main products of glycated PE were determined by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Results showed that the glycation of DPPE formed three major glycated compounds: amadori-glycated-1, 2-dipalmitoyl- sn-glycero -3-phosphoethanolamine (Amadori-DPPE), carboxymethyl-1, 2-dipalmitoyl- sn-glycero -3-phosphoethanolamine (CM-DPPE), and carboxyethyl-1, 2-dipalmitoyl- sn-glycero -3-phosphoethanolamine (CE-DPPE). Amadori-DPPE was identified to generate CM-DPPE through oxidative cleavage of glycated polar head group under high temperature and extended incubation time. Additionally, during thermal processing, retro-aldol reactions of glucose led to the formation of two reactive dicarbonyl intermediates: glyoxal (GO) and methylglyoxal (MGO), both of them reacted with amino group of DPPE to form CM-DPPE and CE-DPPE, respectively. Thus, the formation pathways of CM-PE might involve the irreversible rearrangements of Amadori-PE following oxidative cleavage, as well as the glycation of amino group of PE with GO. CE-PE could only be formed by reaction of PE with MGO. Moreover, the content of CM-DPPE was higher than that of CE-DPPE in the same incubation conditions, which indicated that CM-PE might be a more useful predictive marker for food-derived glycated amino-phospholipid, rather than Amadori-PE, particularly in thermal processed foodstuffs.